2010
DOI: 10.2133/dmpk.dmpk-10-rg-048
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Selective Cyclooxygenase-2 Inhibitor Lumiracoxib on Human Organic Anion Transporters hOAT1 and hOAT3

Abstract: Nonsteroidal anti-inflammatory drugs (NSAIDs) delay renal excretion of antifolate methotrexate by inhibiting human organic anion transporters hOAT1 (SLC22A6) and hOAT3 (SLC22A8). In this study, we performed uptake experiments using Xenopus laevis oocytes to assess the inhibitory effect of selective cyclooxygenase-2 inhibitors on hOAT1 and hOAT3. The uptake of methotrexate into oocytes was increased by the injection of hOAT1 and hOAT3 cRNA, and transport was strongly inhibited by lumiracoxib. The apparent 50% i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The effects of the selective cyclooxyganase-2 inhibitors on the disposition of methotrexate are therefore of interest. Although Hartmann et al reported no effect of lumiracoxib on the disposition of methotrexate in rheumatoid arthritis patients [7], we found that lumiracoxib inhibited human OAT1 (hOAT1) and hOAT3 strongly [8]. The goal of this study was to examine whether lumiracoxib influences renal OATs in vivo.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…The effects of the selective cyclooxyganase-2 inhibitors on the disposition of methotrexate are therefore of interest. Although Hartmann et al reported no effect of lumiracoxib on the disposition of methotrexate in rheumatoid arthritis patients [7], we found that lumiracoxib inhibited human OAT1 (hOAT1) and hOAT3 strongly [8]. The goal of this study was to examine whether lumiracoxib influences renal OATs in vivo.…”
Section: Introductionmentioning
confidence: 78%
“…Sakurai et al reported that hOAT1 and hOAT3 transported PSP [9]. Lumiracoxib exhibited the inhibitory potencies against both transporters, and it was in a competitive manner [8]. Accordingly, it is considered that OAT1 and OAT3, expressed at the basolateral membrane in the proximal epithelial cells, mediated the renal tubular uptake of PSP from blood and that lumiracoxib inhibited it competitively in rats.…”
Section: Resultsmentioning
confidence: 99%
“…The interaction is fatal when high-dose methotrexate therapy is given to a patient [66,67]. Previous studies demonstrated the inhibitory effects of NSAIDs, including cyclooxygenase-2 inhibitors, on methotrexate uptake by OAT1 and OAT3 [68,69,70,71,72]. Some NSAIDs are chiral (Figure 1).…”
Section: Enantioselective Inhibitory Effects Of Drugs On Drug Tranmentioning
confidence: 99%